Mind the Plateau: A Mathematical Modeling Analysis of Long-Term GLP-1 Receptor Agonist Treatment - Patrice A. Hubert; Christopher Coleman; Gregory J. Grosicki; Jessica Kiel; Madelyn Shepherd; Holly F. Lofton; Steven B. Heymsfield; J. Graham Thomas; Nikhil V. Dhurandhar; Satya S. Jonnalagadda (Journal of the Academy of Nutrition and Dietetics, 2026)

Speleothem-based reconstruction of Holocene changes in monsoonal patterns and environmental conditions in Central Brazil - Marcela Eduarda Della Libera; Julio Cauhy; Cintia Stumpf; Roberto V. Santos; Francisco W. Cruz; Nicolas M. Stríkis; Luciana F. Prado; Jean-Sebastian Moquet; Michael Weber; Rebecca Orrison; Hai Cheng; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

Preaccretionary origin of clay minerals in CI chondritic objects? Insights from the Orgueil clay mineralogy and iron oxidation state - J.-C. Viennet; K. Amano; L. Delbes; B. Lavina; F. Hubert; S. Bernard; S. Yaroslavtsev; D. Bessas; A. Chumakov; J.-P. Celse; M. Gounelle; L. Remusat; et al. (Earth and Planetary Science Letters, 2025)

The Martian oxygen green line dayglow: response to solar activity - L. Soret; H. Robin; J.-C. Gérard; L. Gkouvelis; I. Thomas; B. Ristic; Y. Willame; B. Hubert; A.C. Vandaele; J.P. Mason; F. Daerden; M.R. Patel (Icarus, 2025)

Elution revolution: Reversing chiral recognition by swapping d- for l-cellulose - Anna F. Lehrhofer; Markus Bacher; Ivan Melikhov; Irina Sulaeva; Wolfgang Lindner; Michal Kohout; Hiroshi Kamitakahara; Antje Potthast; Thomas Rosenau; Hubert Hettegger (Carbohydrate Polymers, 2025)

Full-Resolution Sentinel-3 Satellite Observations of Phytoplankton Phenology in Optically Complex Waters of the Northern Patagonian Shelf - Maximiliano Arena; Paula Pratolongo; Hubert Loisel; Manh Duy Tran; Daniel S. F. Jorge; Ana Laura Delgado (Estuaries and Coasts, 2025)
In this study, we characterized phytoplankton biomass variability in El Rincón, a shallow and biologically productive coastal region in the Patagonian Continental Shelf. We used as a proxy 7 years (2017–2024) of high-resolution Sentinel-3 OLCI satellite data to capture the fine scale spatio-temporal variability of Chl- a in this region. To obtain Chl- a concentration, we applied a regionally validated algorithm (MuRB&NDCI) which provides more accurate Chl- a estimates compared to traditional algorithms, particularly in optically complex waters. Self-organizing maps (SOM) neural network was applied to identify four distinct bio-geographical regions with unique bloom dynamics. The phenological estimates revealed that phytoplankton blooms typically initiate in fall (March), peak during winter (May–August), and are more pronounced near the Bahía Blanca Estuary (BBE), where nutrient and sediment inputs drive high productivity. The findings presented in this work highlight the utility of Optical Water Class–based algorithms for capturing the fine-scale spatiotemporal variability of Chl- a in coastal systems. This study advances our understanding of phytoplankton dynamics in El Rincón and underscores the importance of customized satellite-derived approaches for monitoring and managing productivity in shallow coastal environments.

Enhanced crude oil degradation observed in sea ice following bioaugmentation with arctic bacteria - Diana Saltymakova; Durell S. Desmond; Alastair F. Smith; María A. Bautista; Eric Collins; Katarzyna Polcwiartek; Nolan Snyder; Teresinha Wolfe; Casey Hubert; Dustin Isleifson; Gary Stern (Marine Environmental Research, 2025)

A mechanistic study on the alleged cellulose cross-linking system: Maleic acid/sodium hypophosphite - Anna F. Lehrhofer; Lukas Fliri; Markus Bacher; David Budischowsky; Irina Sulaeva; Michael Hummel; Thomas Rosenau; Hubert Hettegger (Carbohydrate Polymers, 2024)

P08-07 Prenatal developmental toxicity evaluation of higher olefins in Sprague-Dawley Rats - Q. Shi; J.-C. Carrillo; M. Penman; H. Shen; L. Kamelia; M. Rooseboom; S. Jia; J. Manton; F. Hubert; P. Boogaard (Toxicology Letters, 2024)

Oxidized reducing ends in celluloses: Quantitative profiling relative to molar mass distribution by fluorescence labeling - David Budischowsky; Irina Sulaeva; Fredrik G. Støpamo; Anna F. Lehrhofer; Hubert Hettegger; Anikó Várnai; Vincent G.H. Eijsink; Thomas Rosenau; Antje Potthast (Carbohydrate Polymers, 2024)

Comparison of ocean-colour algorithms for particulate organic carbon in global ocean - Christina Eunjin Kong; Shubha Sathyendranath; Thomas Jackson; Dariusz Stramski; Robert J. W. Brewin; Gemma Kulk; Bror F. Jönsson; Hubert Loisel; Martí Galí; Chengfeng Le (Frontiers in Marine Science, 2024)
In the oceanic surface layer, particulate organic carbon (POC) constitutes the biggest pool of particulate material of biological origin, encompassing phytoplankton, zooplankton, bacteria, and organic detritus. POC is of general interest in studies of biologically-mediated fluxes of carbon in the ocean, and over the years, several empirical algorithms have been proposed to retrieve POC concentrations from satellite products. These algorithms can be categorised into those that make use of remote-sensing-reflectance data directly, and those that are dependent on chlorophyll concentration and particle backscattering coefficient derived from reflectance values. In this study, a global database of in situ measurements of POC is assembled, against which these different types of algorithms are tested using daily matchup data extracted from the Ocean Colour Climate Change Initiative (OC-CCI; version 5). Through analyses of residuals, pixel-by-pixel uncertainties, and validation based on optical water types, areas for POC algorithm improvement are identified, particularly in regions underrepresented in the in situ POC data sets, such as coastal and high-latitude waters. We conclude that POC algorithms have reached a state of maturity and further improvements can be sought in blending algorithms for different optical water types when the required in situ data becomes available. The best performing band ratio algorithm was tuned to the OC-CCI version 5 product and used to produce a global time series of POC between 1997–2020 that is freely available.

Comparing open-source DEM frameworks for simulations of common bulk processes - M. Dosta; D. Andre; V. Angelidakis; R.A. Caulk; M.A. Celigueta; B. Chareyre; J.-F. Dietiker; J. Girardot; N. Govender; C. Hubert; R. Kobyłka; A.F. Moura; et al. (Computer Physics Communications, 2024)

Potential for natural attenuation of crude oil hydrocarbons in benthic microbiomes near coastal communities in Kivalliq, Nunavut, Canada - Meng Ji; Alastair F. Smith; Jayne E. Rattray; Whitney E. England; Casey R.J. Hubert (Marine Pollution Bulletin, 2023)

The brightness of the CO Cameron bands in the martian discrete aurora: A study based on revised cross sections - J.-C. Gérard; L. Soret; B. Hubert; L. Neary; F. Daerden (Icarus, 2023)

Ocean color algorithm for the retrieval of the particle size distribution and carbon-based phytoplankton size classes using a two-component coated-sphere backscattering model - Tihomir S. Kostadinov; Lisl Robertson Lain; Christina Eunjin Kong; Xiaodong Zhang; Stéphane Maritorena; Stewart Bernard; Hubert Loisel; Daniel S. F. Jorge; Ekaterina Kochetkova; Shovonlal Roy; Bror Jonsson; Victor Martinez-Vicente; et al. (Ocean Science, 2023)
The particle size distribution (PSD) of suspended particles in near-surface seawater is a key property linking biogeochemical and ecosystem characteristics with optical properties that affect ocean color remote sensing. Phytoplankton size affects their physiological characteristics and ecosystem and biogeochemical roles, e.g., in the biological carbon pump, which has an important role in the global carbon cycle and thus climate. It is thus important to develop capabilities for measurement and predictive understanding of the structure and function of oceanic ecosystems, including the PSD, phytoplankton size classes (PSCs), and phytoplankton functional types (PFTs). Here, we present an ocean color satellite algorithm for the retrieval of the parameters of an assumed power-law PSD. The forward optical model considers two distinct particle populations: phytoplankton and non-algal particles (NAPs). Phytoplankton are modeled as coated spheres following the Equivalent Algal Populations (EAP) framework, and NAPs are modeled as homogeneous spheres. The forward model uses Mie and Aden–Kerker scattering computations, for homogeneous and coated spheres, respectively, to model the total particulate spectral backscattering coefficient as the sum of phytoplankton and NAP backscattering. The PSD retrieval is achieved via spectral angle mapping (SAM), which uses backscattering end-members created by the forward model. The PSD is used to retrieve size-partitioned absolute and fractional phytoplankton carbon concentrations (i.e., carbon-based PSCs), as well as particulate organic carbon (POC), using allometric coefficients. This model formulation also allows the estimation of chlorophyll a concentration via the retrieved PSD, as well as percent of backscattering due to NAPs vs. phytoplankton. The PSD algorithm is operationally applied to the merged Ocean Colour Climate Change Initiative (OC-CCI) v5.0 ocean color data set. Results of an initial validation effort are also presented using PSD, POC, and picophytoplankton carbon in situ measurements. Validation results indicate the need for an empirical tuning for the absolute phytoplankton carbon concentrations; however these results and comparison with other phytoplankton carbon algorithms are ambiguous as to the need for the tuning. The latter finding illustrates the continued need for high-quality, consistent, large global data sets of PSD, phytoplankton carbon, and related variables to facilitate future algorithm improvements.

Revised age and stratigraphy of the classic Homo erectus-bearing succession at Trinil (Java, Indonesia) - Sander L. Hilgen; Eduard Pop; Shinatria Adhityatama; Tom A. Veldkamp; Harold W.K. Berghuis; Indra Sutisna; Dida Yurnaldi; Guillaume Dupont-Nivet; Tony Reimann; Norbert Nowaczyk; Klaudia F. Kuiper; Wout Krijgsman; et al. (Quaternary Science Reviews, 2023)

Constraints for precise and accurate fluid inclusion stable isotope analysis using water-vapour saturated CRDS techniques - Therese Weissbach; Tobias Kluge; Stéphane Affolter; Markus C. Leuenberger; Hubert Vonhof; Dana F.C. Riechelmann; Jens Fohlmeister; Marie-Christin Juhl; Benedikt Hemmer; Yao Wu; Sophie F. Warken; Martina Schmidt; et al. (Chemical Geology, 2023)

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

COVID-19 in multiple-myeloma patients: cellular and humoral immunity against SARS-CoV-2 in a short- and long-term view - Ivana von Metzler; Julia Campe; Sabine Huenecke; Marc S. Raab; Hartmut Goldschmidt; Ralf Schubert; Holger F. Rabenau; Sandra Ciesek; Hubert Serve; Evelyn Ullrich (Journal of Molecular Medicine, 2022)
Multiple myeloma patients are often treated with immunomodulatory drugs, proteasome inhibitors, or monoclonal antibodies until disease progression. Continuous therapy in combination with the underlying disease frequently results in severe humoral and cellular immunodeficiency, which often manifests in recurrent infections. Here, we report on the clinical management and immunological data of three multiple-myeloma patients diagnosed with COVID-19. Despite severe hypogammaglobulinemia, deteriorated T cell counts, and neutropenia, the patients were able to combat COVID-19 by balanced response of innate immunity, strong CD8+ and CD4+ T cell activation and differentiation, development of specific T-cell memory subsets, and development of anti-SARS-CoV-2 type IgM and IgG antibodies with virus-neutralizing capacities. Even 12 months after re-introduction of lenalidomide maintenance therapy, antibody levels and virus-neutralizing antibody titers remained detectable, indicating persisting immunity against SARS-CoV-2. We conclude that in MM patients who tested positive for SARS-CoV-2 and were receiving active MM treatment, immune response assessment could be a useful tool to help guide decision-making regarding the continuation of anti-tumor therapy and supportive therapy. Key messages Immunosuppression due to multiple myeloma might not be the crucial factor that is affecting the course of COVID-19. In this case, despite pre-existing severe deficits in CD4+ T-cell counts and IgA und IgM deficiency, we noticed a robust humoral and cellular immune response against SARS-CoV-2. Evaluation of immune response and antibody titers in MM patients that were tested positive for SARS-CoV-2 and are on active MM treatment should be performed on a larger scale; the findings might affect further treatment recommendations for COVID-19, MM treatment re-introduction, and isolation measures.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Anaerobic microbial communities and their potential for bioenergy production in heavily biodegraded petroleum reservoirs - Júlia R. de Rezende; Thomas B. P. Oldenburg; Tetyana Korin; William D. L. Richardson; Milovan Fustic; Carolyn M. Aitken; Bernard F. J. Bowler; Angela Sherry; Alexander Grigoryan; Gerrit Voordouw; Stephen R. Larter; Ian M. Head; et al. (Environmental Microbiology, 2020)
Summary Most of the oil in low temperature, non‐uplifted reservoirs is biodegraded due to millions of years of microbial activity, including via methanogenesis from crude oil. To evaluate stimulating additional methanogenesis in already heavily biodegraded oil reservoirs, oil sands samples were amended with nutrients and electron acceptors, but oil sands bitumen was the only organic substrate. Methane production was monitored for over 3000 days. Methanogenesis was observed in duplicate microcosms that were unamended, amended with sulfate or that were initially oxic, however methanogenesis was not observed in nitrate‐amended controls. The highest rate of methane production was 0.15 μmol CH 4 g −1 oil d −1 , orders of magnitude lower than other reports of methanogenesis from lighter crude oils. Methanogenic Archaea and several potential syntrophic bacterial partners were detected following the incubations. GC–MS and FTICR–MS revealed no significant bitumen alteration for any specific compound or compound class, suggesting that the very slow methanogenesis observed was coupled to bitumen biodegradation in an unspecific manner. After 3000 days, methanogenic communities were amended with benzoate resulting in methanogenesis rates that were 110‐fold greater. This suggests that oil‐to‐methane conversion is limited by the recalcitrant nature of oil sands bitumen, not the microbial communities resident in heavy oil reservoirs.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Livestock productivity as indicator of vulnerability to climate hazards: a Mongolian case study - F. Joly; R. Sabatier; B. Hubert; B. Munkhtuya (Natural Hazards, 2018)

Transcriptional profiling by RNA sequencing of black pepper (Piper nigrum L.) roots infected by Fusarium solani f. sp. piperis - Edith C. O. Moreira; Daniel G. Pinheiro; Sheila M. C. Gordo; Simone M. Rodrigues; Elaine Pessoa; Hubert Schaller; Oriel F. de Lemos; Artur Silva; Horacio Schneider; Wilson A. Silva; Iracilda Sampaio; Sylvain Darnet (Acta Physiologiae Plantarum, 2017)

Species-rich grassland can persist under nitrogen-rich but phosphorus-limited conditions - Han F. van Dobben; G. W. Wieger Wamelink; Pieter A. Slim; Jan Kamiński; Hubert Piórkowski (Plant and Soil, 2017)

Energy generation from domestic wastewater using sandwich dual-chamber microbial fuel cell with mesh current collector cathode - J. A. Adeniran; R. Huberts; J. J. De-Koker; O. A. Arotiba; O. F. Olorundare; E. Van-Zyl; S. C. Du-Plessis (International Journal of Environmental Science and Technology, 2016)

Recommendations for Capacity Development in Water Resources Engineering and Environmental Management in Latin America - Helge Bormann; Jürgen Steinbrecher; Ingrid Althoff; Hubert Roth; Julian Baez; Carlos Frank; Mariana Gonzalez; Carlos Huenchuleo; Lisa Lugo; Ricardo Mata; Manuela M. Portela; José M. Reichert; et al. (Water Resources Management, 2016)

Specific leaf area of European Larch (Larix decidua Mill.) - Helga Fellner; Gerald F. Dirnberger; Hubert Sterba (Trees, 2016)

Assisting vascular access surgery planning for hemodialysis by using MR, image segmentation techniques, and computer simulations - M. A. G. Merkx; A. S. Bode; W. Huberts; J. Oliván Bescós; J. H. M. Tordoir; M. Breeuwer; F. N. van de Vosse; E. M. H. Bosboom (Medical & Biological Engineering & Computing, 2013)

Strength and variability of postmating reproductive isolating barriers between four European white oak species - O. Lepais; G. Roussel; F. Hubert; A. Kremer; S. Gerber (Tree Genetics & Genomes, 2013)

In vitro hepatoprotective and antioxidant activities of crude extract and isolated compounds from Ficus gnaphalocarpa - Donfack J. Hubert; Amadou Dawe; Ngueguim T. Florence; Kapche D. W. F. Gilbert; Tchana N. Angele; D. Buonocore; P. Vita Finzi; G. Vidari; Ngadjui T. Bonaventure; Fulvio Marzatico; Moundipa F. Paul (Inflammopharmacology, 2011)

Superior efficacy of new medicines? - Johan C. F. van Luijn; Frank W. J. Gribnau; Hubert G. M. Leufkens (European Journal of Clinical Pharmacology, 2010)

Complex influences of low‐head dams and artificial wetlands on fishes in a Colorado River tributary system - R. J. BEATTY; F. J. RAHEL; W. A. HUBERT (Fisheries Management and Ecology, 2009)
Low‐head dams in arid regions restrict fish movement and create novel habitats that have complex effects on fish assemblages. The influence of low‐head dams and artificial wetlands on fishes in Muddy Creek, a tributary of the Colorado River system in the USA was examined. Upstream, fish assemblages were dominated by native species including two species of conservation concern, bluehead sucker, Catostomus discobolus Cope, and roundtail chub, Gila robusta Baird and Girard. The artificial wetlands contained almost exclusively non‐native fathead minnow, Pimephales promelas Rafinesque, and white sucker, Catostomus commersonii (Lacepède). Downstream, fish assemblages were dominated by non‐native species. Upstream spawning migrations by non‐native white suckers were blocked by dams associated with the wetlands. However, the wetlands do not provide habitat for native fishes and likely inhibit fish movement. The wetlands appear to be a source habitat for non‐native fishes and a sink habitat for native fishes. Two non‐native species, sand shiner, Notropis stramineus (Cope), and redside shiner, Richardsonius balteatus (Richardson), were present only downstream of the wetlands, suggesting a beneficial role of the wetlands in preventing upstream colonisation by non‐native fishes.

Environment‐related life‐history trait variations of the red‐bellied piranha Pygocentrus nattereri in two river basins of the Bolivian Amazon - F. Duponchelle; F. Lino; N. Hubert; J. Panfili; J.‐F. Renno; E. Baras; J. P. Torrico; R. Dugue; J. Nuñez (Journal of Fish Biology, 2007)
Life‐history traits of Pygocentrus nattereri were compared in two populations inhabiting connected tributaries of the upper Madera River: the white water Mamoré River and the clear water Iténez River. As white waters provide better trophic conditions than clear waters, the size at maturity, fecundity, reproductive effort, condition and growth of P. nattereri should be greater in the more productive white water river (Mamoré) than in the less‐productive clear water river (Iténez). Breeding periods were highly seasonal and similar in both rivers and under strong influence of photoperiod. Oocyte size‐frequency distributions, together with the frequent occurrence of recovering females indicated that an individual female spawns at least twice during the breeding season. As predicted, fish of the Mamoré were significantly larger at maturity and had higher fecundity and condition factor values than those of the Iténez. Fish from both rivers matured as yearlings. The higher growth potential of females was better expressed in the Mamoré than in the Iténez, where growth differences between sexes were weak. Females had a significantly better growth in the Mamoré than in the Iténez. The observed life‐history traits associations were consistent with the hypothesis of better trophic conditions in the Mamoré. In addition, previous genetic analyses evidenced that the colonization of the two basins is recent and that extant populations have very similar genetic backgrounds. This suggests that the observed variations in life‐history traits of P. nattereri are not related to historical factors (genetic drift) between two phylogeographically distinct lineages, but rather due to the contrasting environmental conditions in the white and clear waters.

High-energy phosphate metabolism in the calf muscle of healthy humans during incremental calf exercise with and without moderate cuff stenosis - Andreas Greiner; Regina Esterhammer; Dietmar Bammer; Hubert Messner; Christian Kremser; Werner R. Jaschke; Gustav Fraedrich; Michael F. H. Schocke (European Journal of Applied Physiology, 2007)

Chemoenzymatic synthesis of stable isotope labeled UDP-N-[2H]-acetyl-glucosamine and [2H]-acetyl-chitooligosaccharides - Hubert F. Becker; Annie Thellend; Annie Piffeteau; Anne Vidal-Cros (Glycoconjugate Journal, 2006)

Evidence of reproductive isolation among closely related sympatric species of Serrasalmus (Ostariophysii, Characidae) from the Upper Madeira River, Amazon, Bolivia - N. Hubert; F. Duponchelle; J. Nuñez; R. Rivera; J.‐F. Renno (Journal of Fish Biology, 2006)
The delimitation of the Serrasalmus species (Characiformes, Serrasalminae) from the Bolivian Amazon (Amazonas, Madeira) was examined using intron length polymorphism assessed by EPIC‐PCR. The six pairs of primers provided 16 polymorphic loci across the species of the region and the allelic diversity ranged between two and 10 alleles per locus. For each locus, the lack of departure from Hardy‐Weinberg expectations in a large number of the populations analysed and the homogenous distribution of linkage disequilibrium between paralogous loci and loci belonging to different intronic systems provided strong lines of evidence that the 16 amplified loci constituted independent neutral markers. Furthermore, allelic diversity was size‐dependent, thereby indicating that insertion‐deletions occurred frequently but randomly in introns, and that intron length polymorphism was a valid marker for investigating the systematics of piranhas. EPIC‐PCR demonstrated that eight of the nine nominal species of piranha of the Upper Madeira were reproductively isolated and identified a new species that differed from its closest morphological and genetic relatives by seven diagnostic or semi‐diagnostic loci. By contrast, no diagnostic or semi‐diagnostic locus was found between S. spilopleura and S. eigenmanni , nor were their allelic frequencies different, thereby questioning the validity of their biological species status, at least in the Upper Madeira. This study, which was one of the first applications of EPIC‐PCR to a large‐scale molecular systematic purpose, demonstrates that it is a rapid, reliable and cost‐effective tool for elucidating issues pertaining to fish systematics.

Concurrent assessment of fish and habitat in warmwater streams in Wyoming - M. C. QUIST; W. A. HUBERT; F. J. RAHEL (Fisheries Management and Ecology, 2006)
Fisheries research and management in North America have focused largely on sport fishes, but native non‐game fishes have attracted increased attention due to their declines. The Warmwater Stream Assessment (WSA) was developed to evaluate simultaneously both fish and habitat in Wyoming streams by a process that includes three major components: (1) stream‐reach selection and accumulation of existing information, (2) fish and habitat sampling and (3) summarisation and evaluation of fish and habitat information. Fish are sampled by electric fishing or seining and habitat is measured at reach and channel‐unit (i.e. pool, run, riffle, side channel, or backwater) scales. Fish and habitat data are subsequently summarised using a data‐matrix approach. Hierarchical decision trees are used to assess critical habitat requirements for each fish species expected or found in the reach. Combined measurements of available habitat and the ecology of individual species contribute to the evaluation of the observed fish assemblage. The WSA incorporates knowledge of the fish assemblage and habitat features to enable inferences of factors likely influencing both the fish assemblage and their habitat. The WSA was developed for warmwater streams in Wyoming, but its philosophy, process and conceptual basis may be applied to environmental assessments in other geographical areas.

Reproductive partitioning in communally breeding guira cuckoos, Guira guira - Hubert Schwabl; Regina H. F. Macedo; Mariana O. Cariello; Jeff Graves (Behavioral Ecology and Sociobiology, 2004)

Individual female clutch identification through yolk protein electrophoresis in the communally breeding guira cuckoo ( Guira guira ) - Mariana O. Cariello; Hubert G. Schwabb; Raymond W. Lee; Regina H. F. Macedo (Molecular Ecology, 2002)
Avian communal breeding systems generate alternative behavioural strategies for females, resulting in differences in reproductive success. Identifying eggs of different females in such systems is problematic, however, due to egg destruction before incubation, difficulty of capturing adults, and/or inaccuracy of egg identification based on egg morphometry. Here, we describe a technique that uses electrophoresis of yolk proteins to determine egg ownership, which we applied to communally breeding guira cuckoos ( Guira guira ). Validation of the method included identical yolk protein banding patterns in all eggs of the same female, but different patterns in eggs of different females in budgerigars ( Melopsittacus undulatus ), and identical patterns in yolk follicles of the same females in guira cuckoos. We applied the protocol to 195 guira cuckoo eggs from 34 joint nests in 2 years. All multiple guira cuckoo eggs laid on the same day in single nests had distinct banding patterns of yolk proteins, practically eliminating the possibility of more than one female being represented by the same pattern. Some identical banding patterns were repeated in different days within a nesting bout, indicating that some females laid several eggs in shared nests. Identical patterns occasionally occurred in renestings of groups, indicating that some females lay eggs in consecutive nestings. Yolk protein electrophoresis is a useful tool to identify egg maternity in other circumstances, such as polygynous mating systems with joint nests and intraspecific parasitism. Additionally, it is an alternative method for species where electrophoresis of egg white proteins does not show sufficient polymorphism.

Yield response of Lolium perenne swards to free air CO 2 enrichment increased over six years in a high N input system on fertile soil - Markus Daepp; Daniel Suter; José P. F. Almeida; Hubert Isopp; Ueli A. Hartwig; Marco Frehner; Herbert Blum; Josef Nösberger; Andreas Lüscher (Global Change Biology, 2000)
Summary After a step increase in the atmospheric partial pressure of CO 2 (pCO 2 ), the availability of mineral N may be insufficient to meet the plant's increased demand for N. Over time, however, the ecosystem may adapt to the new conditions, and a new equilibrium may be established in the fluxes of C and N. This would result in a higher dry mass (DM) yield response of the plants to elevated pCO 2 . The effect of elevated atmospheric pCO 2 (60 Pa pCO 2 ) was studied in Lolium perenne L. swards with two N fertilization treatments (14 and 56 g m −2 y −1 ) in a six‐year FACE (Free Air Carbon dioxide Enrichment) experiment. In the high N treatment, the input of N with fertilizer considerably exceeded the export of N with the harvested plant material in both CO 2 treatments leading to an apparent net input of N into the ecosystem. Accordingly, the proportion of harvested N derived from 15 N labelled fertilizer N, applied throughout the experiment ( Lolium perenne sward to elevated pCO 2 increased (from 7% in 1993 to 25% in 1998). In parallel, the response of N yield to elevated pCO 2 increased, and the initially negative effect of elevated pCO 2 on specific leaf area (SLA) disappeared. The high N input system seemed to overcome in part an initially limiting effect of N on the yield response to elevated pCO 2 within a few years. In contrast, there was no apparent net input of N into the ecosystem in the low N treatment, because N fertilization just compensated the export of N with the harvested plant material. Accordingly, the proportion of harvested N yield, derived from fertilizer N, which was applied throughout the experiment, remained low. At low N, the availability of mineral N strongly limited plant growth and yield production in both CO 2 treatments; the low yields of DM and N, the low concentration of N in the plant material, and the low SLA reflected this. Although the plants grew under the same environmental conditions and the same management treatment as plants in the high N treatment, the response of DM yields to elevated pCO 2 in the low N treatment remained weak throughout the experiment (5% in 1993 and 9% in 1998). The results are discussed in the context of the sizes of the different N pools in the soil, the allocation of N within the plant and the possible effects on temporal immobilization, and the availability of mineral N for yield production as affected by elevated pCO 2 and N fertilization.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Relationships between boron concentrations and trout in the firehole river, wyoming - Joseph S. Meyer; Ann M. Boelter; Daniel F. Woodward; Jack N. Goldstein; Aïda M. Farag; Wayne A. Hubert (Biological Trace Element Research, 1998)

Effects of elements on blood pressure - Hubert F. Loyke (Biological Trace Element Research, 1997)

Characterization of pars intermedia connections in amphibians by biocytin tract tracing and immunofluorescence aided by confocal microscopy - Koen Jansen; Claudia Fabro; Cristina Artero; Marc Feuilloley; Hubert Vaudry; Aldo Fasolo; Maria F. Franzoni (Cell and Tissue Research, 1997)

The incidence of potato viruses X, Y and S in the Chilota potato collection - C. Theoduloz; J. Sáez-Vásquez; F. Poblete; A. Contreras; E. Hubert; L. Meza-Basso (American Journal of Potato Research, 1992)

Selenium and blood pressure studies in young and adult normotensive, renal, and spontaneously hypertensive animals - Hubert F. Loyke (Biological Trace Element Research, 1992)

ELISA and IHA using two different gonococcal pili as antigens and GCFT using whole gonococci as antigen. Comparison of results obtained by testing sera from patients attending an STD clinic in Rotterdam and from control groups - Arnold P. Oranje; Karin Reimann; Ron V. W. van Eijk; Hubert J. A. Schouten; Annet de Roo; Gerdy J. Tideman; Ernst Stolz; Marc F. Michel (Antonie van Leeuwenhoek, 1982)

The effects of sublethal concentrations of zinc, cadmium and mercury on Euglena - Luigi F. De Filippis; Rüdiger Hampp; Hubert Ziegler (Archives of Microbiology, 1981)